(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Aim: The study was concluded to determine the relationship between selected biomechanical variables with the performance of Pull shot in cricket. Material and Methods: Ten male cricket players who had participated in the Inter-University Cricket tournament or any National level tournament were selected as subjects for this study were selected as subjected for the study. The help of digital photography was used to film the subjects is sagittal & frontal plane of Pull shot performance. Joint point method was used to obtain the values of selected angular kinematics variables from develop stick figures. The performance in Pull shot performance of left-hand Batsmen was recorded based on the three judge’s evaluation the technique of the subjects on selected batting skills were collected. Ten points scale was used. For each batsman’s the average of three judges was considered as the final score. It is hypothesized that there would be no significant relationship between linear & angular kinematic variables and the performance in Batting skills.